Allopolyploidy, diversification, and the Miocene grassland expansion - HODKINSON, TREVOR (My University, 2014)
The role of polyploidy, particularly allopolyploidy, in plant diversification is a subject of debate. Whole-genome duplications precede the origins of many major clades (e.g., angiosperms, Brassicaceae, Poaceae), suggesting that polyploidy drives diversification. However, theoretical arguments and empirical studies suggest that polyploid lineages may actually have lower speciation rates and higher extinction rates than diploid lineages. We focus here on the grass tribe Andropogoneae, an economically and ecologically important group of C4 species with a high frequency of polyploids. A phylogeny was constructed for ca. 10% of the species of the clade, based on sequences of four concatenated low-copy nuclear loci. Genetic allopolyploidy was documented using the characteristic pattern of double-labeled gene trees. At least 32% of the species sampled are the result of genetic allopolyploidy and result from 28 distinct tetraploidy events plus an additional six hexaploidy events. This number is a minimum, and the actual frequency could be considerably higher. The parental genomes of most Andropogoneae polyploids diverged in the Late Miocene coincident with the expansion of the major C4 grasslands that dominate the earth today. The well-documented whole-genome duplication in Zea mays ssp. mays occurred after the divergence of Zea and Sorghum. We find no evidence that polyploidization is followed by an increase in net diversification rate; nonetheless, allopolyploidy itself is a major mode of speciation
Proceedings of the National Academy of Sciences USA
Proceedings of the National Academy of Sciences USA
PUBLISHED
11
Keywords: six hexaploidy; six hexaploidy; Genes & Society; Smart & Sustainable Planet; Biodiversity and Conservation